2010
DOI: 10.1007/s11663-010-9348-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of High-Purity La2O3

Abstract: A separation procedure based on extraction chromatography using the di(2-ethylhexyl) phosphoric acid (D2EHPA) impregnated resin, anion exchange with DIAION SA 10 resin, and oxalate precipitation has been developed for the preparation of high-purity La 2 O 3 in hydrochloric acid media at a high La concentration. The metallic impurities Ce, Pr, Nd, Sm, K, Mg, Ca, Zn, Cu, Co, Mn, Pb, Al, In, and Fe, but not Bi, were removed efficiently from La by extraction chromatography using a D2EHPA impregnated resin. The Bi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The preference of Ln 3+ relative to Fe 3+ or Al 3+ for monomeric Hdehp coordination can be evaluated by the ion exchange results of Hdehp-impregnated resin in the literature. 23 The selectivity order is La 3+ < Ce 3+ < Al 3+ < Sm 3+ < Fe 3+ , which correlates well with the present result of [Al(dehp) 3 ] and partly with the result of [Fe(dehp) 3 ]. Unfortunately, the K d values of Dy 3+ and Yb 3+ were not reported in the literature.…”
Section: Table 1 Distribution Coefficients and Separation Factors On ...supporting
confidence: 88%
“…The preference of Ln 3+ relative to Fe 3+ or Al 3+ for monomeric Hdehp coordination can be evaluated by the ion exchange results of Hdehp-impregnated resin in the literature. 23 The selectivity order is La 3+ < Ce 3+ < Al 3+ < Sm 3+ < Fe 3+ , which correlates well with the present result of [Al(dehp) 3 ] and partly with the result of [Fe(dehp) 3 ]. Unfortunately, the K d values of Dy 3+ and Yb 3+ were not reported in the literature.…”
Section: Table 1 Distribution Coefficients and Separation Factors On ...supporting
confidence: 88%
“…(Lee et al, 2009(Lee et al, , 2010b. The same adsorbent was used, followed by anion exchange and oxalate precipitation to obtain La 2 O 3 of more than 99.9998% purity (Lee et al, 2010a). Amberlite XAD-7 coated with β-glycerophosphate had q m of 33.8 mg/g for La (Gabor et al, 2016).…”
Section: Organic Polymer-based Supportsmentioning
confidence: 99%
“…The Eu(III) extraction from HNO 3 solutions by resins impregnated with a dual-extractant is described in [47]. Moreover, D2EHPA and PC-88A also have advantages of high separation efficiency for REEs [94,95]. Lee et al [96] compared the sorption of REEs on Cyanex 923-, D2EHPA-, and PC88A-impregnated resins and found that D2EHPA-impregnated resins are the most appropriate ones for the separation of Ce, Pr, Nd, and Sm from La for their strong adsorption ability and high separation factors.…”
Section: Rare Earth Elementsmentioning
confidence: 99%
“…The separation of metals is generally achieved by column experiments, and the selectivity factor by SIRs may be controlled by the feed concentration [142], feed pH [89], flow rate [138], support property [66], eluent [92,95], extractant composition [52], preparation method [54], as well as by the column size [94].…”
Section: Equilibrium and Thermodynamics Of Metal Sorption On Sirsmentioning
confidence: 99%